2019
DOI: 10.1016/s1473-3099(18)30493-6
|View full text |Cite
|
Sign up to set email alerts
|

Leave no one behind: response to new evidence and guidelines for the management of cryptococcal meningitis in low-income and middle-income countries

Abstract: Leave no one behind: response to new evidence and guidelines for the management of cryptococcal meningitis in low-income and middle-income countries. 2018 Lancet Infect Dis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
86
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 19 publications
1
86
0
1
Order By: Relevance
“…The most common opportunistic FIs are cryptococcal meningitis (CM), Pneumocystis jirovecii pneumonia (PCP), invasive candidiasis and disseminated aspergillosis [4]. Diagnosis and management of these opportunistic mycosis in RLSs is challenging as standard diagnostic methods and essential antifungal medicines are often absent [5].…”
Section: Introductionmentioning
confidence: 99%
“…The most common opportunistic FIs are cryptococcal meningitis (CM), Pneumocystis jirovecii pneumonia (PCP), invasive candidiasis and disseminated aspergillosis [4]. Diagnosis and management of these opportunistic mycosis in RLSs is challenging as standard diagnostic methods and essential antifungal medicines are often absent [5].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of flucytosine as the mainstay of induction therapy for the treatment of cryptococcal meningitis has been hampered by issues of affordability and sustainable access, particularly in LMICs in Africa (24). This study, using outcomes data from the ACTA trial, has shown that it is cost-effective in the pre-flucytosine cohort, however this was not significant (25).…”
Section: Discussionmentioning
confidence: 97%
“…Generally, cryptococcal meningitis in HIV-infected patients in South Africa is treated initially with intravenous amphotericin B either alone or in combination with oral fluconazole (3). Fluconazole and amphotericin B have been the mainstay of treatment for many years, however recent evidence has shown that the synergistic use of flucytosine improves efficacy and reduces toxicity (4). The World Health Organization (WHO) has updated its guideline to recommend a combination induction phase of one week of intravenous amphotericin B and oral 5-flucytosine or, as an alternative, two weeks of oral flucytosine and fluconazole (5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations